Socioeconomic status and pro-environmentalism: The role of time perspective - TOK QIAN HUI TRICIA, (Institutional Knowledge at Singapore Management University, 2022)
Human actions have caused unprecedented environmental problems, from air and water pollution to climate change. Understanding the demographic influences and psychological antecedents that can motivate more pro-environmentalism (PEV) in individuals could therefore aid in tackling these challenges. The present research aimed to uncover the role that time perspective plays in explaining PEV choices among those of specific socioeconomic contexts. In Study 1, parallel mediation analyses of correlational data (N = 301) found that higher subjective socioeconomic status (SES) was associated with a future time perspective, which in turn positively influenced stronger citizenship and personal intentions to act on climate change, even after controlling for objective SES, age and political ideology. However, the mediation model was non-significant for objective SES measures of income and education. Study 2 (N = 456) took an experimental approach to outline the implications of primed time perspectives on this mediation model, along with added pro-environmental behaviour measures. Although current time perspective was found to moderate a negative relationship between subjective SES in one’s school community on commitment to support environmental organisations significantly more than past time perspective, this did not fully support the hypotheses, nor converge with the results from Study 1. Future research can benefit from developing stronger manipulations for time perspective studies and considering the possible cultural nuances involved in time perspective and PEV.